Green Technology for Sustainable Development: Practice and Experience of Malaysia on Mangrove Forest - Chea, Chiam Chooi (Research Nepal Journal of Development Studies, 2021)
Mangrove forests are important economically and ecologically. In Malaysia, mangrove forests are managed for charcoal, fire wood, and tissue. Due to human disturbance- increasing population or hurricanes –like tsunami, the situation in the rest of the world is similar; most mangrove trees fall beneath the axe or in storms long before reaching their maximum size. Mangroves are one of the most productive wetlands globally and can be found in the intertidal zones along tropical and subtropical areas famous in southeast Asian coastlines. Mangroves are vital in providing breeding and nursery grounds for commercially and recreationally important angle. Mangroves also help to protect coastlines from erosion, storm damage, wave action, and tsunamis. The mangrove ecosystem consists of several significant components, including forest, soil, and the marine ecosystem. To generalize the practice and experience of Mangrove forest management of Malaysia the study has been conducted. Mangrove Forest in Malaysia, Government Initiatives, NGOs Efforts, Private Sector Involvement, and Involvement of Local Community are analysed from the available sources.